Characterization of the ABA Receptor VlPYL1 That Regulates Anthocyanin Accumulation in Grape Berry Skin - Gao, Zhen; Li, Qin; Li, Jing; Chen, Yujin; Luo, Meng; Li, Hui; Wang, Jiyuan; Wu, Yusen; Duan, Shuyan; Wang, Lei; Song, Shiren; Xu, Wenping; et al. (Frontiers in Plant Science, 2018)
ABA plays a crucial role in controlling several ripening-associated processes in grape berries. The best characterized ABA receptors are soluble proteins of the PYR (pyrabactin resistant) / PYL (PYR-like) / RCAR (regulatory component of ABA receptor) family. In this study, the function of a grape encoding PYL1 gene involved in the response to ABA was verified through heterologous expression. High levels of expression of the VlPYL1 gene were found in grape leaf and fruit tissues of the cultivar Kyoho, and the expression of VlPYL1 was increased during fruit development and showed a reduction in ripe berries. Over-expression of VlPYL1 enhances ABA sensitivity in Arabidopsis. Using the transient overexpression technique, the VlPYL1 gene was over-expressed in grape berries. Up-regulation of the VlPYL1 gene not only promoted anthocyanin accumulation but also induced a set of ABA-responsive gene transcripts, including ABF2 and BG3. Although tobacco rattle virus (TRV)-induced gene silencing (VIGS) was not successfully applied in the “Kyoho” grape, the application of the transient overexpression technique in grape fruit could be used as a novel tool for studying grape fruit development.